Muslim society’s perceptions on the needs of android application for learning the meaning of words in Surah Al-Fatihah - Alosman, Abdulrahman; Ismail, Zawawi (IIUM Press, 2022)
The rapid development in technology has brought conventional learning styles to a whole new level of e-Learning, in which learning is not necessarily carried out in the classroom, but through mobile learning or m-learning that transcends the boundaries of time and place. AlQuran learning is not excluded from this fast-paced evolution that has observed the emergence of various Quran-related mobile learning applications today. In view of this emerging trend, this study identified Muslim society's perception on the need for an educational android application for learning the meaning of words in Surah Al-Fatihah. The descriptive method was adopted where a questionnaire was distributed through the social media platform, namely - WhatsApp. 233 responses were recorded from Muslims of various backgrounds and- 11 different nationalities. The results showed that the Muslim respondents have a high level of acceptance for the development of an android application for learning the meaning of words in Surah Al-Fatihah. They also preferred varied functions and a helpful presentation method in the application, and informative learning content that is suited to various levels of the learner. The results of this study can be further used as a base for designing an android application for learning the meaning of words in Surah Al-Fatihah.